Response Time analysis for XAMPP Server based on Different Versions of Linux Operating System - شريف Hawar Othman Sharif; Faraj, Kamaran Hama Ali; Ahmed, Khalid Hassan; Ahmed Al Attar, Tara Nawzad; Hameed, Wafaa Mustafa; Kanbar, Asan Baker (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Automated response time ART) for testing any web page services over different open source operating system OS) versions namely Ubuntu versions which are 12.4, 14.6, 15.10 and 16.04). The response time RT) has an important feature declaration performance analysis in seconds for both of traditionally response time TRT) or physical face-to-face) Businesses, but automated response time ART) is electronically or online tested. The online test achieved by software application namely search engine Page Generated SEPG) in Second. The lowest in seconds by SEPG application which designed by Private home page PHP) is the better result of ART. However, in ART the response time depended on web technology components, one of the web technology components is software that runs over different operating system OS) such as Linux versions. Linux OS versions are installed and ART by Web-based response time WRT) is more advanced than TRT. The example of open source web technology is XAMPP version 1.8. Thus, a XAMPP 1.8 version installed over Linux OS and become LXAMPP after run and tested the LXAMPP over different Linux OS. Linux OS versions are Ubuntu versions 12.04, 14.04, 15.10 and 16.04. All those versions of Ubuntu OS will be testing it by simple search engine Page Generated in Seconds. Finally, the relation between computer architecture and internet architecture became one of our aims.